Sustaining health improvement activities delivered in English professional football clubs using evaluation: a short communication. (2nd September 2016) - Pringle, Andy; Parnell, Daniel; Rutherford, Zoe; McKenna, Jim; Zwolinsky, Stephen; Hargreaves, Jackie
Abstract : It has been suggested that football and communities are inextricably linked. Healthy lifestyles are an important component in maintaining the sustainability of local communities, not least, because a convincing evidence base supports the holistic benefits that can be derived from health-enhancing behaviours, such as regular physical activity. As such, efforts to promote health improvement through sport and physical activity include those interventions delivered in professional sporting settings. Johnman and colleagues (Johnman and Mackie, 'The Beautiful Game') have heralded sports clubs as important venues for the delivery of health improvement interventions for a range of groups across local communities. This includes health improvement activities delivered in professional football club community schemes. While exemplary practice shows how health improvement programmes can be implemented and evaluated, our experience and engagement with professional football club community schemes supports the notion that more needs to be undertaken to help clubs develop monitoring and evaluation strategies in order to assess the impact of their health improvement programmes. In our short communication, we share our plans for helping two professional football clubs develop their monitoring and evaluation strategies for their community health promotion programmes. Potential outcomes emerging from this process are twofold. (1) To help club community schemes in-build and sustain monitoring and evaluation practices within their future health improvement provision. (2) To use the impact and process outcomes emerging from programme evaluations, to successfully secure the necessary resources to sustain future health improvement activities for their local communities. Outcomes emerging from this study will be of interest to football clubs and evaluators alike, as they seek to develop evaluation strategies for their health improvement programmes.